Enhanced amplified spontaneous emission from morphology-controlled organic–inorganic halide perovskite films. Issue 125 (8th December 2015) - Qin, Liang; Lv, Longfeng; Ning, Yu; Li, Chunhai; Lu, Qipeng; Zhu, Lijie; Hu, Yufeng; Lou, Zhidong; Teng, Feng; Hou, Yanbing
Abstract : Perovskite films with well-controlled crystallinity and morphology in a modified sequential deposition process by using solvent mixtures, involving DMF and DMSO, exhibit excellent ASE performances with threshold of 54.10 μJ cm −2 and FWHM of 8.16 nm. Abstract : Organic–inorganic tri-halide perovskites (MAPbX3, where MA = CH3 NH3, and X = Cl, Br, I) have shown promise as laser gain media. The laser characteristics of perovskite films are susceptible to their crystallinity and morphology. Herein, we demonstrate the morphology and crystallinity of perovskite films could be well-controlled in a modified sequential deposition process by using binary solvent mixtures involving N, N -dimethylmethanamide (DMF) and dimethylsulfoxide (DMSO). The highly crystalline and notably smooth MAPbI3 films on glass substrates yield outstanding amplified spontaneous emission (ASE) performance. The binary solvent engineering approach opens up new opportunities for the development of low-cost and high-efficient ASE devices based on perovskite materials.